2020
DOI: 10.1021/acs.jpcc.0c04610
|View full text |Cite
|
Sign up to set email alerts
|

Transition in the Acid–Base Component of Surface Free Energy of Ice upon the Premelting of Its Second Molecular Bilayer

Abstract: Molecular disordering of the ice surface occurs below the bulk melting temperature of 273 K, termed surface premelting. The top-most molecular layer begins gradually premelting at 200 K, and has been linked to its low coefficient of friction through an increase in molecular mobility. The second molecular bilayer premelts around 257 K, but no study has linked this transition to a change in any macroscopic phenomena. Here, we show that the thermodynamic work of adhesion between polydimethylsiloxane and ice chang… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 55 publications
(131 reference statements)
0
3
0
Order By: Relevance
“…Direct influence of premelting of ice at the rubber-ice contact for T > −10 ○ C was presented by Roberts [19] and by Orndorf et al [13], who observed very different types of adhesion between rubber balls and ice above and below ∼ −10 ○ C. In these studies it was also observed that after some minutes dwell in lightly loaded static contact at T > −10 ○ C the rubber sphere made a circular mark in the ice indicating a continuous flow of water away from the contact during stationary contact. The same effect was not observed at T = −20 ○ C.…”
Section: Analysis Of Experimental Data and Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Direct influence of premelting of ice at the rubber-ice contact for T > −10 ○ C was presented by Roberts [19] and by Orndorf et al [13], who observed very different types of adhesion between rubber balls and ice above and below ∼ −10 ○ C. In these studies it was also observed that after some minutes dwell in lightly loaded static contact at T > −10 ○ C the rubber sphere made a circular mark in the ice indicating a continuous flow of water away from the contact during stationary contact. The same effect was not observed at T = −20 ○ C.…”
Section: Analysis Of Experimental Data and Discussionmentioning
confidence: 86%
“…Thus the low friction of ice can be attributed to a combination of frictional heating and ice premelting. However, while many experiments have shown that the free ice-vapor interface undergoes premelting, starting at least 10 ○ C below the bulk melting temperature, there are almost no experimental studies showing that same is true at the interface between ice and another solid [13]. Thus most of the experimental technique used to study the ice-vapor interface cannot be used to study the (buried) interface between ice and another solid.…”
Section: Introductionmentioning
confidence: 99%
“…While our discussion is focused on the substrate of snow, there may be factors of the polar bear paw pad that are specifically adapted to ice. Because seawater contains salt, its presence on the ice will change its adhesion [62] and friction [63] properties compared with pure water and ice. These factors may further complicate prediction of relative friction on ice.…”
Section: Discussion: Relevance To Contact Mechanics On Snowmentioning
confidence: 99%